DIGITAL TRANSFORMATION OF THE EDUCATION SYSTEM IN UZBEKISTAN: CHALLENGES, OPPORTUNITIES, AND FUTURE PROSPECTS (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article provides a comprehensive analysis of the integration of digital technologies within Uzbekistan's education system, emphasizing their development trajectory, key achievements, and persisting challenges. The increasing adoption of digital tools has significantly influenced the educational landscape, reshaping traditional teaching methodologies and improving both the accessibility and effectiveness of learning processes for students across various academic levels.The study delves into the transformative role of digitalization, highlighting its impact on pedagogical approaches, curriculum structuring, and administrative efficiency within educational institutions. Additionally, it explores the extent to which modern technological advancements, such as artificial intelligence, big data analytics, and cloud-based learning platforms, are being incorporated into the national education strategy.Furthermore, the paper examines the challenges associated with digital transformation, including disparities in technological infrastructure, the digital divide between urban and rural educational institutions, and the necessity for continuous teacher training to effectively implement digital learning tools. Special attention is given to the ongoing reforms and government initiatives aimed at fostering a more inclusive and technology-driven educational ecosystem.By analyzing the current trends and future prospects of digital education in Uzbekistan, this research contributes to the broader discourse on the role of digitalization in shaping contemporary educational frameworks. The findings underscore the need for a strategic and well-coordinated approach to ensure that digital transformation in education maximizes its potential benefits while addressing the existing gaps and limitations.